Obtención de dos tipos de enzimas pectinasa (cáscara de naranja) celulasa (cáscara de plátano) y su evaluación en la producción de pulpa de manzana (Malus domestica) y pera (Pyrus communis) en los laboratorios académicos de la carrera de ingeniería agroindustrial de la Universidad Técnica de Cotopaxi en el periodo 2014 – 2015 - Avilés Muso, Norma Soledad (2016)
This research had as objective to obtain two types of enzymes pectinase and cellulose from orange and banana peel for the production of apple pulp (Malus domestic) and pear (Pyrus communis). It had two enzyme extracts with an enzymatic activity of pectinase of 2,18 U, that is to mean. 1U is the amount of enzyme, which liberates 1 μ mol of galacturonic acid per minute to 4.1 pH, 50 ° C, and enzyme activity of cellulose is 3.18, that is to mean 1U is the amount of enzyme that frees 1 μ mole of glucose beta in one hour with pH 5.0, to 37 ° C. It did the organoleptic analysis to different treatments where it was evaluated color, smell, taste, texture and acceptability, that survey was performed to 148 students of Agro industrial Engineering Major, at Technical University of Cotopaxi. With the data obtained was made in the statistical program Infostat /L and Excel applying a scheme of analysis of variance with a complete design at random (DBCA) in factorial arrangement 2 * 3.